Membaca Kesiapan Pondok Pesantren dalam Menghadapi Era Volatilitas, Uncertainty, Complexity, Ambiguity (VUCA) - Yusuf, M. (Program Studi Manajemen Pendidikan Islam (MPI) STAI Nahdlatul Ulama (STAINU) Malang, 2025)
This article extensively discusses how Islamic boarding schools (pondok pesantren) confront the challenges of the Volatility, Uncertainty, Complexity, and Ambiguity (VUCA) era. In the context of rapid changes and environmental uncertainty, Islamic boarding schools play a crucial role in preparing the younger generation. The research background emphasizes the urgency of Islamic boarding schools' adaptation to VUCA conditions to ensure the continuity of education and Islamic values. The applied research method is library research, involving a review of relevant literature to delve into the concept of VUCA and the approaches taken by Islamic boarding schools to address it. The research aims to explore the strategies and innovations implemented by Islamic boarding schools in response to the challenges of the VUCA era. The research findings indicate that Islamic boarding schools have adopted various initiatives, including curriculum enhancements, staff training, and the implementation of educational technology. The practical implications of these findings provide profound insights into how Islamic boarding schools can strengthen their Islamic education amid the complexities of the VUCA era. This article contributes significantly to understanding and optimizing the role of Islamic boarding schools in educating the younger generation in this challenging era.